Digital fundamentals - Floyd, Thomas L. (Prentice Hall, 1994)
Packed with full-color photographs, illustrations, graphs, and more, this acclaimed introduction to digital fundamentals emphasizes troubleshooting and applications using real devices. It provides thorough, up-to-date coverage of digital fundamentals, from basic concepts to microprocessors. Supports clear, accurate explanations of theory with superior exercises, examples, and visual aids. Includes only the mathematics readers need to understand certain concepts. Is accompanied by an Electronics Workbench circuits disk that is keyed to problems and activities in the book. Offers Electronics Workbench tutorials for many of the chapters on a book, specific Web, site.